A Statistical Simulation for the Profitability of Banks: A Study - Okeke, Chinedu; Nwude, E. Chuke (International Journal of Economics and Financial Issues, 2018)
This study investigated the profitability of quoted banks alongside the risk content. The relevant models as enunciated in the current literatures for determining the return as well as risk were employed. The findings of the study showed that GTB is the most profitable bank in Nigeria with respect to return on shareholders' funds and return on assets for the entire 15-year study period. Sterling bank is crowned the most profitable bank in Nigeria with respect to return on capital employed. Keywords: return on equity, return on assets, return on capital employed, banks, profitability JEL Classification: G2